Acinetobacter baylyi regulates type IV pilus synthesis by employing two extension motors and a motor protein inhibitor - Courtney K. Ellison (Nature Portfolio, 2021)
Type IV pili (T4P) are retractile appendages used by bacteria for DNA uptake and other purposes. T4P extension is thought to occur through the action of a single motor protein, PilB. Here, Ellison et al. show that T4P synthesis in Acinetobacter baylyi depends not only on PilB but also on an additional, distinct motor, TfpB.